The intricate path of energy conservation in quantum mechanics: exploring coherent population return and laser–matter interaction - Peralta Conde, Alvaro (The European Physical Journal Plus, 2024)
This manuscript explores how a seemingly straightforward inquiry, emerging from the widely accepted semiclassical description of laser–matter interaction, concretely from a well-known adiabatic technique as coherent population return (CPR), can pose a challenge to our comprehension of a fundamental principle in Physics such as energy conservation. Throughout our investigation to resolve this apparent paradox, we have delved into fundamental concepts, thereby deepening our understanding of the aspects inherent to the formalism of Quantum Mechanics. We emphasize that the significance of attaining a conclusive answer extends beyond the answer itself, encompassing the illuminating journey undertaken to reach it. Consequently, our work holds educational value as it aims to foster a deeper understanding of the phenomenon by elucidating the process employed. This approach not only aids students in grasping the subject matter but also enhances our own understanding of laser–matter interaction and the counterintuitive phenomena that continuously defied our understanding of Quantum Mechanics.
Keywords: energy conservation; quantum mechanics; laser–matter interaction; CPR